Analisis Kepuasan Masyarakat terhadap Pembuatan Akta Kelahiran di Depok, Jawa Barat - Windyani, Amita Rizka; Hubeis, Aida Vitayala S.; Fahmi, Idqan (Universitas Brawijaya, Indonesia, 2014)
Birth certificate is a basic civil right that should be granted to every citizen. Dinas Kependudukan dan Pencatatan Sipil (Disdukcapil) as a birth certificate registration organizers seek to provide excellent service with attention to people's satisfaction. This study aim to analyse the commitment of Disdukcapil in the service of registration of birth certificate, analyse the level of public satisfaction about Disdukcapil's public service, and formulate a strategy to improve the quality of service. The research method is descriptive analysis. The data used are primary and secondary derived from observations, interviews, and questionnaires. Internal officer's perceptions were analyzed using the test of customer service and customer-focused test characteristics. Customers's perceptions were analyzed using SERVQUAL method, Importance Performance Analysis, and Customer Satisfaction Index. The results show that Disdukcapil structural officers have had community-oriented in the implementation of public service. Characteristics that stand out in the application of quality management is readiness to find and eliminate the problems of the people on birth certificate registration. Servqual analysis results show that acceptable performance is still below people's expectations so that the gap is negative. Importance-performance analysis show that the attributes need immediate attention is the service support materials, attitude immediately provide service and a helpful attitude when busy. Overall community satisfaction index had reached Satisfied level.